Are the TiO2 NPs a "Trojan horse" for personal care products (PCPs) in the clam Ruditapes philippinarum?. (October 2017) - Sendra, M.; Pintado-Herrera, M.G.; Aguirre-Martínez, G.V.; Moreno-Garrido, I.; Martin-Díaz, L.M.; Lara-Martín, P.A.; J, Blasco
Abstract: In recent years, increasing quantities of personal care products (PCPs) are being released into the environment. However, data about bioaccumulation and toxicity are scarce; and extraction and analytical approaches are not well developed. In this work, the marine clam Ruditapes philippinarum, selected as model organism, has been employed to investigate bioaccumulation, antioxidant enzyme activities and DNA damage due to exposure to TiO2 nanoparticles and bulk TiO2 (inorganic compounds that are frequent components of PCPs, plastics, paints and coatings, foods and disinfectant water treatments). We have also studied the joint effect of both forms of inorganic TiO2 combined with four organic compounds (mixture exposures) commonly used in PCPs: an antimicrobial (triclosan), a fragrance (OTNE) and two UV filters (benzophenone-3 and octocrylene). Bioaccumulation of the inorganic compound, TiO2, was almost immediate and constant over exposure time. With respect to the organic compounds in mixtures, they were mediated by TiO2 and bioaccumulation is driven by reduced size of the particles. In fact, nanoparticles can be considered as a vector to organic compounds, such as triclosan and benzophenone-3. After a week of depuration, TiO2 NPs and TiO2 bulk in clams showed similar levels of concentration. Some organic compounds with bioactivity (Log Kow >3), like OTNE, showed low depuration after one week. The joint action of the organic compound mixture and either of the two forms of TiO2 provoked changes in enzyme activity responses. However, for the mixtures, DNA damage was found only after the depuration period. Graphical abstract: Highlights: Exposure to mixed treatments hindered the activity of defensive enzyme systems in digestive gland. Bioaccumulation is rapid for organic and inorganic PCPs; depuration is slow for inorganic PCPs. TiO2 NPs act as a "trojan horse" for bioaccumulation of some organic compounds inside clams.